UNUSUAL PRESENTATION OF INTRACRANIAL MASS EXTRUDING OUT OF SKULL - Rafiq, Mirza Faisal Ahmed; Zaman, Khaleeq uz; Ibrahim, Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Scalp masses are commonly seen in clinical practice. They range from simple sebaceous cyst to malignant neoplasms. Clinical presentation is straight forward in most of the cases. Simple subcutaneous swelling till erosion of scalp and skull all can occur. However very few intracranial masses present with exophytic scalp swelling. This is because they have to erode dura, thick skull bone and all the layers of scalp to appear out on scalp. It is very unusual that an intracranial mass present like a scalp swelling. Some of the intracranial masses have tendency to erode skull. Dermoid & meningioma are among the most common.